Investment behavior of the population in modern conditions - A. O. Sevruk; V. A. Varfolomeeva (Путеводитель предпринимателя, 2025)
The article focuses on aspects that influence the investment behavior of the population in the financial market. Theoretical approaches to the investment behavior of the population, behavioral features are studied. A comparative characteristic of the types of financial instruments for investments of individuals is shown. Statistical data on investment preferences of the population for 2022–2024 are considered. The authors draw a conclusion on the investment behavior of the population in different periods of the economic situation.